Activation of Water at the Active‐Site Cavity of Zinc Phthalocyanine with Tris(pentafluorophenyl)borane. Issue 7 (10th February 2020) - Ikeuchi, Takuro; Kudo, Ryota; Yoshii, Tatsuya; Kobayashi, Nagao; Kitazawa, Yu; Kimura, Mutsumi
Abstract : Activation of water bound with Zn 2+ has attracted much attention as an artificial model of natural enzymes. Despite many attempts, water activation accompanied with a change in the coordination geometry of Zn 2+ in complexes remains a challenge. In this study, we discover a new structure that is composed of partially protonated zinc phthalocyanine (ZnPc), hydroxide ion, and tris(pentafluorophenyl)borane (TPFB). The coordination of TPFB with water bounded with ZnPc results in the dissociation of water, and the dissociated proton from water moves to one nitrogen atom of the phthalocyanine ring through the intramolecular proton transfer. On the basis of this reaction, the coordination geometry transforms from a five‐coordinated to a distorted tetrahedral species. The Zn 2+ ‐bound hydroxide nucleophile in the ZnPc‐TPFB complex attacks amide of ε‐caprolactam to produce hydrolyzed 6‐aminohexanoic acid in toluene. Abstract : Coordination of tris(pentafluorophenyl)borane with water bound to zinc phthalocyanine results in the dissociation of water, and the dissociated proton from water moves to one nitrogen atom of the phthalocyanine ring through intramolecular proton transfer.